BENEFITS AND LIMITATIONS OF INTERNATIONAL ARBITRATION IN INTELLECTUAL PROPERTY LAW DISPUTES - Његослав Јовић (Годишњак Правног факултета у Бањалуци)
In this paper, the author analyzes the benefits and limitations of international arbitration in disputes that are subject to intellectual property rights. Intellectual property law disputes have special characteristics. In the event of a dispute with an international element, there is a problem with the jurisdiction of state courts due to the principle of the territoriality of intellectual property rights. The titular of the right must initiate court proceedings in all countries individually, leading to delays in procedures, multiplication of costs and uneven judicial practice. For these reasons, the author analyzes alternative dispute resolution through arbitration to determine whether this method of dispute resolution is more acceptable to foreign courts. The author particularly pays attention to the WIPO Center for Arbitration and Mediation as a permanent arbitration institution whose primary activity is the resolution of disputes in the field of intellectual property rights.